Application of telenursing as a nursing care delivery model in improving treatment adherence and glycemic control: A scoping review - Yuli Wahyuni; Maria Komariah; Irman Somantri (JKP (Jurnal Keperawatan Padjajaran), 2023)
Background: Diabetes mellitus is one of the chronic diseases that cause  the highest mortality and high medical costs;, therefore medication adherence and glycemic control are important  in disease management, one of which is through telenursing.